Introduction: Historical geographies of internationalism, 1900–1950. (November 2015) - Hodder, Jake; Legg, Stephen; Heffernan, Mike
Abstract: This introduction to a special issue on historical geographies of internationalism begins by situating the essays that follow in relation to the on-going refugee crisis in Europe and beyond. This crisis has revealed, once again, both the challenges and the potential of internationalism as a form of political consciousness and the international as a scale of political action. Recent work has sought to re-conceptualise internationalism as the most urgent scale at which governance, political activity and resistance must operate when confronting the larger environmental, economic, and strategic challenges of the twenty-first century. Although geographers have only made a modest contribution to this work, we argue that they have a significant role to play. The essays in this special issue suggest several ways in which a geographical perspective can contribute to rethinking the international: by examining spaces and sites not previously considered in internationalist histories; by considering the relationship between the abstractions of internationalism and the geographical and historical specificities of its performance; and by analysing the interlocking of internationalism with other political projects. We identify, towards the end of this essay, seven ways that internationalism might be reconsidered geographically in future research through; its spatialities and temporalities; the role of newly independent states; science and research; identity politics; and with reference to its performative and visual dimensions.